Using English Talk Show Videos on Youtube to Enhance Listening Skill: A Learners’ Voices - Setiani, Aneu Agnes; Apandi; Suminar, Ratna Prasasti (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
This study explores how students use YouTube videos of English talk shows to improve their listening comprehension as learners' voices. This study combined a narrative research design with a qualitative methodology. Interviews and observation were used to gather data. Two University of Cirebon students majoring in English education who were familiar with YouTube and used English talk shows to improve their listening skills were the research participants. Overall, the results indicate that students have a positive attitude toward using English talk show videos, which are helpful in three ways. Students first listened to a variety of English dialects and learned about both formal and informal language use by watching English talk show videos, which served as their authentic listening materials. Second, they used talk show videos to enhance their listening skills because they can enrich their vocabulary, identify the topic in spoken language, and differentiate English accents. Third, students used English talk show videos to motivate themselves because they thought English talk show videos are fun ways to practice their listening skills.